From “Obstetrical Violence” Complaints to “Respectful Maternity Care”: The Complaints Commissioner as Facilitator of Organizational Change - Lemoine, Marie-Eve; Sigman, Harvey; Jimenez, Vania; Laliberté, Maude (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
In this case study, we describe an approach to dealing with a complicated, systemic, and multifaceted organizational issue: perceptions of obstetrical violence in the continuum of maternal care from antepartum care, birthing, to post-natal care.